Endocrine, Metabolic and Pharmacological Effects of Thyronamines (TAM), Thyroacetic Acids (TA) and Thyroid Hormone Metabolites (THM) – Evidence from in vitro, Cellular, Experimental Animal and Human Studies - Homuth, Georg; Lietzow, Julika; Schanze, Nancy; Golchert, Janine; Köhrle, Josef (Experimental and Clinical Endocrinology & Diabetes, 2020)
Thyroid hormone metabolites (THM) with few or no iodine substituents such as 3,5-T2, the thyronamines 3-T1AM and T0AM, and their oxidation products, the thyroacetic acids (TA) formed by monoamine oxidases, have recently attracted major interest due to their metabolic actions which are in part distinct from those of the classical thyromimetic hormone T3, the major ligand of T3 receptors. This review compiles and discusses in vitro effects of 3,5-T2, TAM and TA reported for thyrocytes, pancreatic islets and hepatocytes as well as findings from in vivo studies in mouse models after single or repeated administration of pharmacological doses of these agents. Comparison of the 3,5-T2 effects on the transcriptome with not yet published proteome data in livers of obese mice on high fat diet indicate a distinct anti-steatotic effect of this THM. Furthermore, uptake, metabolism, and cellular actions via various receptors such as trace amine-associated receptors (TAAR), alpha-adrenergic, GPCR and T3 receptors are discussed. Studies on postulated pathways of biosynthesis of 3-T1AM, its effects on the HPT-axis and thyroid gland as well as insulin secretion are reviewed. 3-T1AM also acts on hepatocytes and interferes with TRPM8-dependent signaling in human cell lines related to the eye compartment. Human studies are presented which address potential biosynthesis routes of 3,5-T2 and 3-T1AM from THM precursors, especially T3. The current state of diagnostic analytics of these minor THM in human blood is portrayed comparing and critically discussing the still divergent findings based on classical immunoassay and recently developed liquid-chromatography/mass- spectrometry methods, which allow quantification of the thyronome spectrum from one single small volume serum sample. The clinical perspectives of use and potential abuse of these biologically active THM is addressed.
Keywords: thyroid hormone metabolite; 3-iodo-thyronamine; 3; 5-diiodothyronine; thyrocyte; pancreatic islet; liver; high fat diet; steroid metabolism; cholesterol metabolism; thyroacetic acid